MANAJEMEN KINERJA PEGAWAI PADA SEKSI PENYELENGGARAAN HAJI DAN UMRAH KEMENTRIAN AGAMA PASAMAN BARAT - Gustia Hazuli; Khadijah Nurani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This research is motivated by problems in employee performance, including lack of accuracy, lack of understanding of work, and the problem of employee delays when entering work. The purpose of conducting this research is to find out what kind of employee performance management of the Hajj and Umrah organizing section in Pasaman Barat district. This study uses a qualitative method with a descriptive approach, because here the author decribes the performance of employess while working by collecting data obtained from interviews. Data collection techniques using observation, interviews, and documentation. The results of the study show that performance management of employess in the hajj and umrah organizing section is good. Starting from work experience and knowledge possessed by employees obtained while studying so that the results obtained are in accordance with expectations, the organization of activities made by the organization went well because the employees had extensive knowledge and made neat strategies, the appreciation given also determines that the employee can do their job well, and the honest and fair attitude that exists in employees when they work makes the company run well